Using Tracers to Quantify Drilling Water Influence and Obtain Representative Groundwater Samples. Issue 1 (12th November 2015) - McCaughey, M.C.; Divine, Craig E.; Gefell, Michael J.; McGrane, Sean
Abstract: This paper describes a practical field method of using applied tracers to determine how much purging is required to collect representative groundwater samples after the introduction of drilling water during borehole advancement. In general, the approach involves adding a tracer of known concentration to the drilling water and then measuring the tracer in the purge water until the tracer concentration declines to a defined target level. If necessary, the dilution effects of residual drilling water can be quantified, and the measured contaminant concentration can be corrected based on the measured tracer concentration. A project example is presented to demonstrate that this method is straightforward and reliable and that applied tracers can be used to quantify the influence of residual drilling water on formation water quality while also ensuring that purge times and volumes are not unnecessarily large.